(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
Environmental education and education for the environment play an important role in sustainability today. Environmental education provided by higher education institutions has an important impact on preparing the next generation for a green society. Over time, various problems occurring in nature (the thinning of the ozone layer, global warming, acid rain, water, air and soil pollution) have made people realize the need to treat nature more responsibly. but human responsibility for environmental protection is both individual and primarily collective. Conservation involves cooperation and support at the local, regional, national and other levels, especially at the international level.